Analisis Pengaruh Pembangunan Kota Baru Moncongloe Terhadap Mata Pencaharian Masyarakat - iswan pasaribun; Rudi Latief; Emil Salim Rasyidi (Fakultas Teknik Universitas Bosowa, 2022)
In the research that the author conducted was about the influence of the development of the New City of Moncongloe on the livelihoods of the people. This study aims to determine whether there is an influence between the development of the moncongloe new city and people's livelihoods. This study uses two variables, namely the Progress of Moncongloe New Town Development and Community Livelihoods. The analytical approach used in this research is the Quantitative Approach. In this study, the r-test analysis tool (Pearson Correlation) was used to determine the effect of the development of the moncongloe new town on the livelihoods of the people in Moncongloe Village, Moncongloe District, Maros Regency. Based on the results of the Pearson Correlation Analysis , the conclusion of this study is that the development of the New City of Moncongloe experiences land changes every year, namely the change of green open space into residential land. The development of the New City of Moncongloe has a significant effect, very strong with a negative correlation value on farmers. This means that the increasing progress of Moncongloe New Town Development will have an impact on the decreasing number of people who make a living as farmers.